Shock metamorphism of clay minerals on Mars by meteor impact - Joseph R. Michalski; Timothy D. Glotch; Lonia R. Friedlander; M. Darby Dyar; David L. Bish; Thomas G. Sharp; John Carter (Geophysical Research Letters)
Abstract A large fraction of clay minerals detected on Mars by infrared remote sensing represent materials exhumed from the subsurface by meteor impact, begging the question of whether the infrared features used to detect the clays are affected by shock associated with the impacts. We used X‐ray diffraction and infrared and Mössbauer spectroscopy to evaluate the mineralogy of five clay minerals after experimentally shocking them to six shock pressures from ~10 to 40 GPa. The shocked clays exhibit three main relevant shock effects: (1) an overall decrease in infrared spectral contrast in the impact‐fragmented materials, (2) oxidation of Fe in ferrous clays, and (3) loss of some spectral structure in relatively well‐ordered clays such as kaolinite. Other than the widespread oxidation of ferrous clays, shock metamorphism likely has little effect on the accurate interpretation of clay mineralogy on Mars from remote sensing data. However, we are able to identify rare cases of extreme shock in some Martian clay deposits.